Analisis Pemanfaatan Limbah Las Karbit sebagai Substitusi Sebagian Semen untuk Peningkatan Mutu dan Beton Berkelanjutan - Debby Sinta Devi; Fathoni Usman; M Farhan Nurhadi (Jurnal Konstruksi, 2025)
Increasing cement consumption in line with growing construction activities has led to higher building costs and rising carbon dioxide (CO2) emissions, both of which contribute to global warming. One potential alternative material is carbide welding waste, a residue generated from welding processes that is often underutilized and frequently becomes waste with the potential to pollute the environment. This study aims to analyze the effect of using carbide welding waste as a partial cement substitute on the physical and mechanical properties of concrete, particularly its water absorption (absorptivity) and compressive strength. The method used is an experimental approach with substitution variations of 6%, 9%, and 12% of carbide welding waste relative to the cement weight. The test results show that these substitution percentages produce different effects on the characteristics of the concrete. A 9% substitution provides the most optimal outcome, with a compressive strength of 28.95 MPa and the lowest absorption value of 2.4417%. These values are superior to those of normal concrete without substitution, which has a compressive strength of 25.64 MPa and an absorption value of 2.7001%. At 6% substitution, the compressive strength reaches 26.74 MPa with an absorption value of 2.5481%, while at 12% substitution, concrete quality declines, with compressive strength dropping to only 22.50 MPa and absorption increasing to 3.2416%. The findings demonstrate that carbide welding waste can be used as a partial cement substitute, with the optimal percentage being 9%.